Intracellular Signal Transduction and Modification of the Tumor Microenvironment Induced by RET/PTCs in Papillary Thyroid Carcinoma - Menicali, Elisa; Moretti, Sonia; Voce, Pasquale; Romagnoli, Serena; Avenia, Nicola; Puxeddu, Efisio (Frontiers in Endocrinology, 2012)
RET gene rearrangements (RET/PTCs) represent together with BRAF point mutations the two major groups of mutations involved in papillary thyroid carcinoma (PTC) initiation and progression. In this review, we will examine the mechanisms involved in RET/PTC-induced thyroid cell transformation. In detail, we will summarize the data on the molecular mechanisms involved in RET/PTC formation and in its function as a dominant oncogene, on the activated signal transduction pathways and on the induced gene expression modifications. Moreover, we will report on the effects of RET/PTCs on the tumor microenvironment. Finally, a short review of the literature on RET/PTC prognostic significance will be presented.